(3OjhGf GdSQj GdQaGAs - (3GdnqSpQqj Hf CMeO Hf GdSQj GdcfOj, CHh GdMSf GdnqQnqaGA,J (B366 (3g` s ((3GdMSf Hf Ydj Hf EHQGgje s)
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA bGajI GdCda GdebUhQI Hbhdg(B: (3hdjd QMjH GdHGY eO QhGbg Ydi GdCab MJi pNjd aj MdJj Kcdi s
(3BNQgG (B:s
(3ef bUjOI jeGRM ajgG YHOGdMejO GdehUdj hde CQ eKdg ojrQ pHj YbhbkG ajOYhg GdhQi nHQnqG MajG s
(3GdOjhGf eQJH Ydi GdbhGajs
(3efbhdI ef fSNI HNW Ydj Hf GdMSf Hf CHj OLGfI GdeUQjs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B208s
Keywords: (3GdCOHs